Global impact of the COVID‐19 pandemic on cytopathology practice: Results from an international survey of laboratories in 23 countries. Issue 12 (27th October 2020) - Vigliar, Elena; Cepurnaite, Rima; Alcaraz‐Mateos, Eduardo; Ali, Syed Z.; Baloch, Zubair W.; Bellevicine, Claudio; Bongiovanni, Massimo; Botsun, Pavlina; Bruzzese, Dario; Bubendorf, Lukas; Büttner, Reinhard; Canberk, Sule; et al.
Abstract : Background: To the authors' knowledge, the impact of the coronavirus disease 2019 (COVID‐19) pandemic on cytopathology practices worldwide has not been investigated formally. In the current study, data from 41 respondents from 23 countries were reported. Methods: Data regarding the activity of each cytopathology laboratory during 4 weeks of COVID‐19 lockdown were collected and compared with those obtained during the corresponding period in 2019. The overall number and percentage of exfoliative and fine‐needle aspiration cytology samples from each anatomic site were recorded. Differences in the malignancy and suspicious rates between the 2 periods were analyzed using a meta‐analytical approach. Results: Overall, the sample volume was lower compared with 2019 (104, 319 samples vs 190, 225 samples), with an average volume reduction of 45.3% (range, 0.1%‐98.0%). The percentage of samples from the cervicovaginal tract, thyroid, and anorectal region was significantly reduced ( P < .05). Conversely, the percentage of samples from the urinary tract, serous cavities, breast, lymph nodes, respiratory tract, salivary glands, central nervous system, gastrointestinal tract, pancreas, liver, and biliary tract increased ( P < .05). An overall increase of 5.56% (95% CI, 3.77%‐7.35%) in the malignancy rate in nongynecological samples during the COVID‐19 pandemic was observed. When the suspicious category was included, the overall increase was 6.95% (95% CI, 4.63%‐9.27%). Conclusions: The COVID‐19 pandemic resulted in a drastic reduction in the total number of cytology specimens regardless of anatomic site or specimen type. The rate of malignancy increased, reflecting the prioritization of patients with cancer who were considered to be at high risk. Prospective monitoring of the effect of delays in access to health services during the lockdown period is warranted. Abstract : The coronavirus disease 2019 (COVID‐19) pandemic has resulted in a drastic reduction in the total number of cytology specimens obtained regardless of anatomic site or specimen type. The rate of malignancy has increased, reflecting the prioritization of patients with cancer who are considered to be at high risk. Prospective monitoring of the effect of delays on access to health services during the lockdown period is warranted.